Polycyclic aromatic hydrocarbons (PAHs) in air and vegetation: case study at three selected toll stations along North South Expressway in Johor, Malaysia - Azhari, Azliyana (2012)
Polycyclic aromatic hydrocarbons (PAHs) from vehicular emission are products of the incomplete combustion of organic fuel, and are usually attached to the particulate matter from the emission and can caused pollution and hazard to human health due to its carcinogenic, mutagenic and teratogenic characteristics. The objective of this study is i) to determine the concentration PAHs in the air of sampling area, ii) to determine the concentration PAHs in vegetation, iii) to determine the relationship of concentration of PAHs in plants and air of sampling area and iv) to study the different composition of PAHs in different species of plants to determine the potential biomonitoring agent. The study is carried out at three toll stations along PLUS’ North-South Expressway in Johor. Air sample and plant leaves sample collected were extracted with ultrasonic agitation in dichloromethane and fractionated according to polarity before submitted to gas chromatography – mass spectrometry analysis to determine the concentration of the PAHs compounds. Spearman’s rank correlation test was carried out using SPSS to determine the correlation between concentration of PAHs in air and plant leaves sample. Seven PAHs were identified and quantified in the atmospheric sample and plant leaves sample. Those PAHs were acenaphtylene (ACN), phenanthrene (PHE), fluorene (FL), pyrene (PY), chrysene (CHR), benzo[a]anthracene (BaA), and benzo[a]pyrene (BaP). Significant correlation at 0.05 level (2-tailed) was observed in samples of Ficus microcarpa, Cordyline fruticosa, Hibiscus spp., and Ixora coccinea with the value 0.622, 0.643, 0.680 and 0.608 respectively. The positive correlation shows that the plants have capabilities to absorb organic pollutants from the environment. Based from this research, the most suitable species to be introduced into the environment as a biomonitoring agent and to be further studied as a medium for low and medium level pollution bioremediation is Ficus microcarpa, Cordyline fruticosa, and Ixora coccinea